Reliability of ambulatory urodynamics in patients with spinal cord injuries12. Issue 4 (21st September 2012) - Vírseda, Miguel; Salinas, Jesús; Esteban, Manuel; Méndez, Santiago
Abstract Objective To determine the test–retest repeatability of the urodynamic parameters commonly utilized in ambulatory urodynamics (AM) for patients with neurogenic lower urinary tract dysfunction (NLUTD). Methods A test–retest repeatability study was performed on 64 consecutive patients with stable spinal cord injuries who underwent two AM studies 24 hr apart. Results The mean age was 43.2 years, with 47 males and 17 females. A significant intraclass correlation coefficient (ICC) was found between the two studies with respect to the functional bladder capacity (FBC; 0.74), the maximum detrusor pressure during the involuntary detrusor contraction (PdetmaxIDC; 0.84), and the post‐void residual (PVR; 0.76). Of note, the ICC of the end filling detrusor pressure (Pdetfill) was not significant (0.25). The correlation with respect to the presence of involuntary detrusor contraction (IDC) was significant but low (κ = 0.40). Based on the logistic regression analysis, the variables that influenced the concordance with respect to the presence of the IDC were PdetmaxIDC (directly) and Pdetmax (inversely). The variable that that influenced the concordance with respect to PdetmaxIDC was PVR (directly). The variable that influenced the concordance with respect to PVR was the FBC (directly). Conclusions AM is reliable for the reproduction of the main urodynamic parameters investigated in patients with NLUTD, except for the end filling detrusor pressure, which was a non‐reliable parameter. The concordance of AM can be improved primarily by taking into account the values of the maximum detrusor pressure during involuntary detrusor contraction (PdetmaxIDC). Neurourol. Urodynam. 32: 387–392, 2013. © 2012 Wiley Periodicals, Inc.